Quantitative Logic and Soft Computing 2016 Proceedings of the 4th International Conference on Quantitative Logic and Soft Computing (QLSC2016) held at Hangzhou, China, 14-17 October, 2016 - Fan, Tai-He.; Chen, Shui-Li.; Wang, San-Min.; Li, Yong-Ming.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is the proceedings of the Fourth International Conference on Quantitative Logic and Soft Computing (QLSC2016) held 14-17, October, 2016 in Zhejiang Sci-Tech University, Hangzhou, China. It includes 61 papers, of which 5 are plenary talks( 3 abstracts and 2 full length talks). QLSC2016 was the fourth in a series of conferences on Quantitative Logic and Soft Computing. This conference was a major symposium for scientists, engineers and practitioners to present their updated results, ideas, developments and applications in all areas of quantitative logic and soft computing. The book aims to strengthen relations between industry research laboratories and universities in fields such as quantitative logic and soft computing worldwide as follows: (1) Quantitative Logic and Uncertainty Logic; (2) Automata and Quantification of Software; (3) Fuzzy Connectives and Fuzzy Reasoning; (4) Fuzzy Logical Algebras; (5) Artificial Intelligence and Soft Computing; (6) Fuzzy Sets Theory and Applications.
Keynote Speakers -- Quantitative Logic and Uncertainty Logic -- Automata and Quantification of Software -- Fuzzy Connectives and Fuzzy Reasoning -- Fuzzy Logical Algebras -- Fuzzy Set Theory and Applications -- Artificial Intelligence and Soft Computing.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence